Kajian Asia Tenggara: Antara Narasi, Teori, dan Emansipasi - Achmad Firas Khudi; Iqra Anugrah (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2013)
As an academic discipline, modern Southeast Asian Studies (SEA Studies) faces three main challenges. First of all, there is still a huge gap in scholarship and publication between the West-based and Southeast Asia-based SEA Studies. Secondly, SEA Studies is often in a dilemmatic position between the push for generalization of mainstream social sciences and the anti-causality stance of various strands of Postmodernism. Thirdly, in general there is a decline of SEA Studies in the West especially in North America. However, recent developments in SEA Studies, namely a possibility for an emancipatory SEA Studies, the shifting center of gravity for SEA Studies from North America to Asia-Pacific and the expanding higher education sector in Indonesia might present some opportunities for the development of a Southeast Asia-based SEA Studies in the future.